SATU DIMENSI, DUA WAJAH: MEMETAKAN ORIENTASI KEUANGAN GENERASI Z DI SULAWESI TENGGARA ANTARA PERBANDINGAN SOSIAL DAN KEHATI-HATIAN FINANSIAL - Wa Ode Sartika; Samsul Bachri Soamole; Sitti Hadijah; Harpiang Wardingsih; Muhammad Suriyadarman Rianse; Muhammad Fajar Salemaku (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine whether social comparison orientation, financial prudence, and financial management behavior form distinct constructs or merge into a single dimension among Generation Z in Southeast Sulawesi. The research method involved a questionnaire survey distributed to Gen Z respondents, analyzed through confirmatory factor analysis, the Fornell -Larcker criterion, the heterotrait-monotrait ratio, and Harman’s single-factor test. The results indicate that discriminant validity failed across all construct pairs due to overlapping item contents. Consequently, the three constructs merged into a single bipolar continuum of financial orientation, ranging from social comparison to prudence. Furthermore, this financial orientation behavior is cross-segmental, showing no significant differences across demographic backgrounds. These findings highlight the critical importance of discriminant validity testing in financial behavior research & underscore the need for comprehensive financial education interventions to mitigate social comparison pressures.